Mini Greenhouse: Efforts to Improve Environmentally Friendly Agricultural Skills for Students of Pondok Pesantren Al Asror - Mukhibad, Hasan; Widiyanto; Kusumantoro; Nurkhin, Ahmad; Anisykurlillah, Indah; Wahyuningrum, Indah Fajarini Sri; Raharjo, Teguh Hardi; Sulhadi (Indonesian Journal of Devotion and Empowerment, 2025)
Pondok pesantren are increasingly paying attention to environmental issues, sustainability, and the promotion of the Sustainable Development Goals (SDGs), as well as striving to provide life skills for students (Santri) through training and self-development activities. This article explains the impact of utilizing a mini greenhouse to improve students’ agricultural skills through a community service program at Pondok Pesantren Al Asror Semarang, targeting 15 students. The activities were carried out over five months (May to September 2025) in the form of training and assistance in using the mini greenhouse. The training introduced the mini greenhouse and its benefits, after which the students worked together to prepare and build it within the pondok pesantren environment. The next activities included plant cultivation, starting from seed sowing, planting, and caring for the plants until harvest time, under the guidance and supervision of the community service team. The students were highly enthusiastic and motivated to make use of the mini greenhouse, and they received support from the pondok pesantren leaders to enhance their life skills. The students then continued using the mini greenhouse for organic vegetable cultivation, starting from sowing to harvest time.